The Impact of Biosolid Application on Soil and Native Plants in a Degraded Brazilian Atlantic Rainforest Soil - Sampaio, Thalita Fernanda [UNESP]; Guerrini, Irae Amaral [UNESP]; Luiz Otero, Xose; Macias Vazquez, Felipe; Bogiani, Julio Cesar; Oliveira, Fernando Carvalho; Gava, Jose Luis; Ciol, Marcia A.; Littke, Kim M.; Harrison, Robert B. (Springer, 2016)
We conducted a field experiment to determine whether application of biosolids (municipal sewage sludge) to degraded areas of the Brazilian Atlantic rainforest had the potential to contaminate native forest species with trace metals in the sandy soils of the region. Treatments consisted of 0, 2.5, 5, 10, 15, and 20 dry Mg biosolids ha(-1), with nine native pioneer, secondary, and climax tree species assessed for metal uptake: capixingui, aroeira-pimenteria, canafistula, cedro-rosa, mutamba, angico-vermelho, copaiba, jatoba, and jequitiba. Biosolid application did not have a statistically significant effect on metal concentrations in soil, and Cd was the only metal with increased availability. No increased metal uptake was seen in tree foliage sampled at 6 and 12 months after application. Additional longer-term study is recommended; however, the results of this study indicate biosolids could be used in Atlantic rainforest reclamation in degraded sandy soils with little impact on soil accumulation and tree uptake of trace metals.
Keywords: Sewage sludge; Heavy trace metals; Typic Quartzipsamment; Residuals reuse